Energy poverty and government subsidies in China - Jiafeng Gu (Energy Policy, 2023)
Identifying the policy effect of government subsidies on families is beneficial to alleviate household energy poverty. This study first builds a Propensity Score Matching–Difference-in-Differences (PSM-DID) model and empirically tests the impact of government subsidies on household energy poverty in China based on China Family Panel Studies data from 2016 to 2018. The results show that household energy poverty is considered to have obvious regional differences. Moreover, the results indicate that government subsidies can reduce the probability of household energy poverty by 38.1%. However, the effect of government subsidies in alleviating household energy poverty will vary depending on the specific household situation. It is concluded that subsidies provided by the Chinese government to households can effectively alleviate household energy poverty. Finally, some policy recommendations are proposed based on the results of the empirical analysis.